2021
DOI: 10.1021/acsomega.1c01677
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study on the Feasibility of Pyrolysis Biomass Char Applied to Blast Furnace Injection and Tuyere Simulation Combustion

Abstract: Basic property analysis is the most comprehensive evaluation of metallurgical characteristics of blast furnace injection fuel. In this study, the basic properties of 16 types of pyrolysis biomass char samples were comprehensively investigated; the results showed that components harmful to a blast furnace, such as the ash content and alkali metal content of Jiangsu Suzhou woodblock char (B3), Jiangsu Changzhou branch char (B8), Jiangsu Zhangjiagang bamboo char (B10), and Jiangsu Zhangjiagang coconut shell char … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 41 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…The research [16] explores the viability of using pyrolysis biomass char in blast furnace injection and tuyere simulation combustion. The study delves into the potential of biomass char as a sustainable alternative fuel source in industrial processes.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The research [16] explores the viability of using pyrolysis biomass char in blast furnace injection and tuyere simulation combustion. The study delves into the potential of biomass char as a sustainable alternative fuel source in industrial processes.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In addition, the kinematic viscosity of biodiesel is within the acceptable range (1.9 to 6.0 mm 2 /s), and the flash point of all biodiesels is more than 150 • C [8,9], which makes it safer than petroleum-based diesel. Furthermore, it was found that mixing different percentages of bio-fuel with ordinary diesel fuel reduces exhaust gases such as carbon monoxide (CO) and particulate manners (PM) [10,11]. However, there is still uncertainty about the ability to reduce the emissions of carbon dioxide (CO 2 ) and nitrogen oxides (NO and NO 2 ) [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…PCI is the most effective in reducing the use of coke in BF. It is assumed that PC has 75% of carbon, while coke, coke breeze, anthracite, and recarburizer have 85% carbon [11]. A biochar sample derived from wood residues (from combustion at 600-1000 • C) containing 85-87% of C has characteristics similar to coals used in BFs [12].…”
mentioning
confidence: 99%
“…Since the properties of the coke mixture require the creation of sufficient load-bearing strength in order to maintain the permeability of the layer, the mixture can be achieved with a maximum of 20% substitution with biochar, reducing CO 2 emissions by 0.33 t CO 2 /t [11].…”
mentioning
confidence: 99%